Reformulation of Legal Criteria for Mandatory Rehabilitation for Drug Abusers in the Indonesian Criminal Justice System - Sunardi; Tina Amelia (Indonesian Journal Publisher, 2026)
This study aims to analyze and reformulate the legal criteria for mandatory rehabilitation for drug abusers in the Indonesian criminal justice system, which currently lacks clear and operational parameters. The method used is normative legal research, with a legislative and conceptual approach, based on a review of Law Number 35 of 2009 concerning Narcotics, its implementing regulations, and the principles of criminal law and human rights. The results indicate that although mandatory rehabilitation norms have been established, their implementation still faces various problems, including the dominance of official discretion, disparity in sentencing, the use of possession articles against users, and the weakness of integrated assessments as stipulated in the 2014 Joint Regulation of 7 Institutions concerning the Management of Narcotics Addicts. The absence of clear legal criteria creates legal uncertainty and substantive injustice, contradicting the principles of the 1945 Constitution of the Republic of Indonesia. Therefore, this study proposes reformulating the legal criteria for mandatory rehabilitation based on objective parameters, strengthening integrated assessments, and integrating institutions within a double-track system framework to create a fairer, more certain, and recovery-oriented criminal justice system.